Smallholder Tree Growing for Rural Development and Environmental Services Lessons from Asia - Snelder, Denyse J.; Lasco, Rodel D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Recent history reveals both that the large-scale reforestation projects of the 20th century have often been less successful than anticipated, and that tree growing by smallholders – as an alternative means to combat deforestation and promote sustainable land use – has received relatively little attention from the scientific and development communities. Taking a first step to addressing that balance, this collection of peer-reviewed papers adopts a comparative approach to explore the potential role that tree growing by farmers can play in sustainable forest management. The goal of this approach is to identify common threads and to start to develop a framework for future research and practice. Presenting case studies from the Philippines and comparative data from a number of Asian countries the book reveals that farmer tree growing has the potential to play a significant role in sustainable forest management, and discusses the surrounding issues which must be addressed in order to realise this potential. The book is primarily aimed at research scientists and graduate students interested in relevant aspects of forestry, agroforestry, agricultural diversity, natural resource management and conservation in agricultural landscapes, as well as those involved in sustainable development and international development studies. It will also provide a valuable reference for professionals, managers, consultants, policy makers and planners dealing with issues in sustainable development, natural resource management, land use change issues and participatory approaches to resource management.
Smallholder Tree Growing: Introduction -- Smallholder Tree Growing in South and Southeast Asia -- Smallholder Tree Growing for Rural Development: Practices and Adoption -- Smallholder Tree Growing in Philippine Back Yards: Homegarden Characteristics in Different Environmental Settings -- Tree Growing on Farms in Northeast Luzon (The Philippines): Smallholders’ Motivations and Other Determinants for Adopting Agroforestry Systems -- Dudukuhan Tree Farming Systems in West Java: How to Mobilize Self-Strengthening of Community-Based Forest Management? -- The Adoption of Smallholder Rubber Production by Shifting Cultivators in Northern Laos: A Village Case Study -- Agroforestation of Grasslands in Southeast Asia: WaNuLCAS Model Scenarios for Shade-Based Imperata Control During Tree Establishment -- Smallholder Tree Growing for the Market: Economics, Policies and Institutes -- Over-Regulated and Under-Marketed: Smallholders and the Wood Economy in Isabela, The Philippines -- Can Smallholder Tree Farmers Help Revive the Timber Industry in Deforested Tropical Countries? A Case Study from Southern Philippines -- The Reforestation Value Chain for the Philippines -- The Potential of Sustainable Forestry Certification for Smallholder Tree Growing -- Exploring the Agroforestry Adoption Gap: Financial and Socioeconomics of Litchi-Based Agroforestry by Smallholders in Rajshahi (Bangladesh) -- Growing ‘The Wood of The Gods’: Agarwood Production in Southeast Asia -- Local Vulnerability, Project Risk, and Intractable Debt: The Politics of Smallholder Eucalyptus Promotion in Salavane Province, Southern Laos -- Smallholder Tree Growing for Environmental Services: Practices and Potentials -- Improving Productivity, Profitability and Sustainability of Degraded Grasslands Through Tree-Based Land Use Systems in the Philippines -- Restoration of Philippine Native Forest by Smallholder Tree Farmers -- Human-Altered Tree-Based Habitats and Their Value in Conserving Bird and Bat Diversity in Northeast Luzon, The Philippines -- From Principles to Numbers: Approaches in Implementing Payments for Environmental Services (PES) in the Philippines -- Values and Services of Nitrogen-Fixing Alder Based Cardamom Agroforestry Systems in the Eastern Himalayas -- Perceptions of Ethnic Minorities on Tree Growing for Environmental Services in Thailand -- Smallholder Tree Growing: Potentials and Challenges -- Farmer Tree Planting Barriers to Sustainable Forest Management -- Future Challenge: A Paradigm Shift in the Forestry Sector.
Keywords: Forestry; Forestry management; Agriculture; Environmental management; Marketing; Agricultural economics; Forestry; Forestry Management; Agriculture; Environmental Management; Marketing; Agricultural Economics